Effectiveness of Self-monitoring Training by Islamic Contemplation Approach on Self-restraint among Female Students of Tehran University - Fatimah Nosrati; Sorayya Jafari-Ardi; Bagher Ghobari-Bonab (Shahid Beheshti University of Medical Sciences, 2020)
For downloading the full-text of this article please click here. Background and Objective: University students are the intellectual human resources of any society and they are the prospects of their country. Paying attention to their mental, spiritual, social, cultural and physical health will provide the ground for realization of a dynamic and healthy life in the future. The purpose of the present study was to determine the effectiveness of self-monitoring training using the Islamic contemplation approach on self-restraint among female students of Tehran University. Methods: This study adopted a quasi-experimental pretest and posttest control group design. The statistical population consisted of all students of University of Tehran who were studying in the educational year 2017. A sample of 30 female students from Tehran University was selected using available sampling method. They were randomly assigned to two experimental (15) and a control group (15). Participants in the experimental group received an Islamic-contemplation self-monitoring training program in eight (one-and-a-half-hour) sessions. A self-restraint questionnaire Gatfordson and Hirschi was used to collect data. Data were analyzed using covariance analysis. In this study, all the ethical considerations have been observed and no conflict of interest was reported by the authors. Results: The results showed that the female students in the experimental group had significantly higher self-control scores than the control group on the post-test and the hypothesis of the study concerning the effectiveness of self-monitoring training by Islamic contemplation approach on self-restraint of Tehran University students was confirmed (P>0/01). Conclusion: Based on the findings, group religious-spiritual intervention had a positive effect on the internal and self-control power of female students, and this intervention could be used to improve the psychological resources in increasing students' self-restraint. For downloading the full-text of this article please click here. Please cite this article as: Nosrati F, Jafari-Ardi S, Ghobari-Bonab B. Effectiveness of Self-monitoring Training by Islamic Contemplation Approach on Self-restraint among Female Students of Tehran University. Journal of Pizhūhish dar dīn va salāmat. 2020;6(2):20-36. https://doi.org/10.22037/jrrh.v6i2.22988